Can dynamic imaging, using 18F-FDG PET/CT and CT perfusion differentiate between benign and malignant pulmonary nodules? - Marin, Aleksander (Radiology and oncology (Ljubljana), 2021)
Background. The aim of the study was to derive and compare metabolic parameters relating to benign and ma- lignant pulmonary nodules using dynamic 2-deoxy-2-fluorine-18fluoro-D-glucose (18F-FDG) PET/CT, and nodule perfu- sion parameters derived through perfusion computed tomography (CT). Patients and methods. Twenty patients with 21 pulmonary nodules incidentally detected on CT underwent a dynamic 18F-FDG PET/CT and a perfusion CT. The maximum standardized uptake value (SUVmax) was measured on conventional 18F-FDG PET/CT images. The influx constant (Ki) was calculated from the dynamic 18F-FDG PET/CT data using Patlak model. Arterial flow (AF) using the maximum slope model and blood volume (BV) using the Patlak plot method for each nodule were calculated from the perfusion CT data. All nodules were characterized as malignant or benign based on histopathology or 2 year follow up CT. All parameters were statistically compared between the two groups using the nonparametric Mann-Whitney test. Results. Twelve malignant and 9 benign lung nodules were analysed (median size 20.1 mm, 9-29 mm) in 21 patients (male/female = 11/9; mean age +- SD: 65.3 +- 7.4; age range: 50-76 years). The average SUVmax values +- SD of the benign and malignant nodules were 2.2 +- 1.7 vs. 7.0 +- 4.5, respectively (p = 0.0148). Average Ki values in benign and malig- nant nodules were 0.0057 +- 0.0071 and 0.0230 +- 0.0155 min-1, respectively (p = 0.0311). Average BV for the benign and malignant nodules were 11.6857 +- 6.7347 and 28.3400 +- 15.9672 ml/100 ml, respectively (p = 0.0250). Average AF for the benign and malignant nodules were 74.4571 +- 89.0321 and 89.200 +- 49.8883 ml/100g/min, respectively (p = 0.1613). Conclusions. Dynamic 18F-FDG PET/CT and perfusion CT derived blood volume had similar capability to differentiate benign from malignant lung nodules.
Keywords: benign pulmonary nodules; benigni pljučni vozliči; CT perfusion; CT perfuzija; malignant pulmonary nodules; maligni pljučni vozliči; polimorfizmi